1989
DOI: 10.1111/j.1151-2916.1989.tb05990.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Water into Silica Glass at Low Temperature

Abstract: Diffusion of water into silica glass was measured in the temperature range of 200" to 750°C by treating the glass in air containing a constant water vapor pressure aind analyzing the concentration profile using a Fourier transform infrared spectrometer. In the short-time diffusion heat treatments, the surface concentration was lower and the apparent diffusion coefficient was higher than the corresponding steady-state values. The temperature dependence of the steady-state diffusion coefficient showed two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 14 publications
9
101
1
Order By: Relevance
“…The timeframe to dissolve a layer of Mg with the initial thickness h 0 is defi ned by the material itself, as given in Equation (21) . Figure 2 b shows an encapsulation layer of MgO with initial experiments, such as 0.069 nm s − 1 in the citric acid-Na 2 HPO 4 buffer system with PH 7.4 [ 12 ] and 0.096 nm s − 1 in conventional chloride solution.…”
Section: Double-layer Reactive Diffusionmentioning
confidence: 99%
“…The timeframe to dissolve a layer of Mg with the initial thickness h 0 is defi ned by the material itself, as given in Equation (21) . Figure 2 b shows an encapsulation layer of MgO with initial experiments, such as 0.069 nm s − 1 in the citric acid-Na 2 HPO 4 buffer system with PH 7.4 [ 12 ] and 0.096 nm s − 1 in conventional chloride solution.…”
Section: Double-layer Reactive Diffusionmentioning
confidence: 99%
“…Native and exposed ashes were run both with and without vacuum drying. Infrared analysis of water in glass and applications in the geological sciences has a long and extensive history, including the studies of fluid and melt inclusions (Bartholomew & Butler 1980;Wakabayashi 1989;Newman et al, 1986;Metrich and Wallace, 2008). Determining water concentration in a small and irregular glass fragments or mica (e.g.…”
Section: Isotope Analysesmentioning
confidence: 99%
“…3) Some researchers have reported that water can collapse the composition of glass under extreme conditions, and borosilicate glass is no exception. [4][5][6][7][8][9] In addition to water, other elements in drug solutions are known to induce the collapse of glass surfaces. Ennis et al 10) evaluated the tendencies of delamination from borosilicate glass vials based on the fact that the cidofovir injectable drug product formed glass delamination, and they concluded that the high pH of the solution enhanced the corrosive attack on the inner surface of the glass container, resulting in delamination.…”
mentioning
confidence: 99%